KEBIJAKAN PUBLIK PERTAHANAN NEGARA INDONESIA - Asma Aulia Zikra Hanum Ardi; Timbul Siahaan; IB Putra Jandhana (DAS Institute, 2022)
This research is analytical descriptive research. The purpose of this study is to explain and analyze Indonesia's national defense public policy from time to time. Formulating national defense public policies with appropriate and adaptive strategies in the implementation of national defense is an absolute requirement for realizing the independence of national defense and security. Public policy on national defense can guide and provide the nation in the future in facing various threats, disturbances, obstacles, and challenges that come and go, both military and non-military threats. Therefore, it is necessary to study the evolution of national defense public policy based on Indonesia's leadership so that it can be a reference in improving national defense in the future. The results of the study indicate that the more renewable National Defense Public Policy is following technological developments and the types of threats that are increasingly unpredictable, namely the National Defense Policy of 2018 and Presidential Regulation No. 8 of 2021 concerning the General Policy of National Defense for 2020-2024 which produces various strategic products including the National Defense Doctrine of 2021, National Defense Posture of 2021, National Defense Strategy of 2021, National Defense White Paper of 2021, MEF Adjustments, and MEF's TNI for 2020-2024